2012
DOI: 10.1590/s0102-09352012000200002
|View full text |Cite
|
Sign up to set email alerts
|

Trânsito de bovinos nos estados do Mato Grosso e Mato Grosso do Sul, Brasil

Abstract: Compreender a dinâmica de atuação dos frigoríficos contribui para a definição de prioridades e para o estabelecimento de barreiras sanitárias, em caso de uma possível emergência sanitária, ou para a busca de estratégias para a erradicação de enfermidades bovinas. O objetivo deste estudo foi analisar e descrever as áreas de abrangência dos principais municípios que possuem frigoríficos de abate de bovinos com serviço de inspeção federal nos estados do Mato Grosso e Mato Grosso do Sul, revelando as peculiaridade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 12 publications
0
8
0
1
Order By: Relevance
“…Cerrado was the biome with the most intense cattle trade pattern (Fig.4), what presumably explains the fact that the largest number of slaughterhouses in Mato Grosso was in the Cerrado. Capanema et al (2012) found four counties that were important poles in the cattle movement for slaughter in Mato Grosso, three located in the Cerrado and one in the Amazon. Although the median herd size in the Pantanal was the largest (Table 2), the least intense cattle trade pattern was observed there, which could be related to the smallest area, the lowest number of farm premises and slaughterhouses, and also to the environmental constraints since it is a floodplain.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cerrado was the biome with the most intense cattle trade pattern (Fig.4), what presumably explains the fact that the largest number of slaughterhouses in Mato Grosso was in the Cerrado. Capanema et al (2012) found four counties that were important poles in the cattle movement for slaughter in Mato Grosso, three located in the Cerrado and one in the Amazon. Although the median herd size in the Pantanal was the largest (Table 2), the least intense cattle trade pattern was observed there, which could be related to the smallest area, the lowest number of farm premises and slaughterhouses, and also to the environmental constraints since it is a floodplain.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the Amazon has the larger area and number of premises, but a lower number of slaughterhouses and animals moved. The cover extent of Amazon forest(Morton et al 2011) could partially explain the lower volume of animal trade in comparison to the Cerrado.Other cattle movement studies were performed in the Brazilian states of Pernambuco(Silva Júnior et al 2017), Mato Grosso and Mato Grosso do Sul(Capanema et al 2012), and Paraná and Santa Catarina(Felipe et al 2013).Capanema et al…”
mentioning
confidence: 99%
“…Other cattle movement studies were performed in the Brazilian states of Mato Grosso (NEGREIROS, 2010;CAPANEMA et al, 2012;CIPULLO, 2013;GRISI-FILHO et al, 2013;CIPULLO et al, 2016), Mato Grosso do Sul (CAPANEMA et al, 2012), Paraná, and Santa Catarina (FELIPE et al, 2013). The state of Mato Grosso is part of the Central West region in Brazil, and, in 2014, was responsible for 33.5% of the Brazilian cattle herd along with its Central West neighboring states, Mato Grosso do Sul and Goiás (BRASIL, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In Mato Grosso and Mato Grosso do Sul GTAs were analyzed in order to identify the municipalities that received the highest amount of cattle destined for slaughterhouses, classifying them as the municipal centers for slaughter (CAPANEMA et al, 2012). In Paraná and Santa Catarina GTAs were analyzed to identify the micro-regions that receive the most cattle, classifying them as the central regions for slaughter or slaughter destinations (FELIPE et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have cited that animal traffic is an important risk factor for disease dissemination (BIGRAS-POULIN et al, 2007;CAPANEMA et al, 2012). This raises the possibility of CL transmission through movement and close contact between the infection sources, susceptible vectors, and interferences at the agglomeration site, as well as the traffic between region's goat and sheep breeding farms to the animal fairs.…”
Section: Discussionmentioning
confidence: 99%